The Impact of Social Media Marketing Elements on Consumer Brand Engagement, Brand Awareness, and Brand Image - Annisa Rosdiana; Indrawati Indrawati (Transpublika Publisher, 2024)
This study explores the influence of social media marketing (SMM) elements—entertainment, customization, interaction, electronic word-of-mouth (eWOM), and trendiness—on consumer-brand engagement and brand image. Using an online survey, data were gathered from 273 Instagram followers of @officialgamboeng in Indonesia, who had consumed Gamboeng tea products within the past three months. Partial least squares structural equation modeling (PLS-SEM) was applied to analyze the relationships between SMM elements, consumer-brand engagement, brand awareness, and brand image. The findings reveal that trendiness significantly enhances consumer-brand engagement, boosting brand awareness and brand image. However, customization shows no notable impact on consumer-brand engagement. As this study is cross-sectional and focuses on a single local tea brand, its findings may have limited applicability to other contexts. Future research could extend the study to multiple brands and regions to enhance generalizability. Practical recommendations include creating content that educates consumers about Gamboeng's unique qualities, such as ingredient quality and production processes, and leveraging diverse social media platforms like TikTok and Threads. Strengthening the brand's story by emphasizing its values and history could further enhance consumer recognition and retention. Marketers can improve consumer-brand engagement by generating trendy content, fostering interaction, and encouraging positive eWOM. These efforts can strengthen brand associations and consumer loyalty. This study contributes to branding literature by highlighting the critical role of trendiness in brand-building and reaffirming social media as an effective channel for engaging consumers and promoting brand knowledge.